Be smart, act fast, get rich : - Payne, Charles V. (John Wiley & Sons, 2007)
Explain how to use fundamental analysis along with technical analysis to discover undervalued stocks, provide you with the knowledge and tools needed to stop emotionally sabotaging your stock market investing efforts, show you how to assemble portfolios that are positioned to outperform the market and make you rich, teach you how to be an investor who owns stocks for the kind of gains that buy real comfort and peace of mind—rather than a trader who simply flips stocks for pennies.